BURNOUT AKADEMIK GURU PESERTA PENDIDIKAN PROFESI - Rahman, Diniy Hidayatur; Simon, Irene Maya; Multisari, Widya (JURKAM: Jurnal Konseling Andi Matappa, 2020)
The study aims to determine the academic burnout of teachers taking Professional Teacher Education (Pendidikan Profesi Guru) at Universitas Negeri Malang (UM) based on their gender, marital status, and employment status. This is the first study mapping the academic burnout of teachers participating in professional education with various demographic variables. The study applied comparative design. 360 teachers who took their professional education at UM in the even semester 2019 participated in the study. Research data was collected using a demographic questionnaire and School Burnout Inventory that was adapted into Bahasa Indonesia and professional education context. The exploratory factor analysis and Cronbach's Alpha were applied to test the validity and reliability of the instrument. the Mann-Withey U Test and Kruskal Wallis were also used to analyze the data. The results showed that there are no differences in the academic burnout of the subjects in term of gender, marital status, and employment status.